English Language Learning and the Identity of Muslim Undergraduate Students in Pakistan - Sultan, Sameera (Register Journal, 2025)
This study examines how English language learning influences the identity of Muslim undergraduate students at a private university in Pakistan, considering its significance in national, religious, and global contexts. Using a qualitative research approach, data was collected through a survey of students from a well-reputed university in Karachi. A questionnaire developed by Yihong et al. (2007) measured identity changes using a five-point Likert scale across six categories: self-confidence, additive change, subtractive change, productive change, split change, and zero change. Grounded in bilingualism, identity formation, and sociolinguistics theories, this study explores language as a cultural and religious marker, shaping self-perception and community affiliation. Findings indicate that English proficiency enhances self-confidence and global identity but also creates tensions in maintaining Islamic and cultural heritage. While most students experience additive identity changes—retaining both English and their native language—some undergo subtractive changes, weakening ties with their native culture and religious traditions. Hybrid identities emerge as students navigate between English, Urdu, and Islamic discourse, reflecting the complex role of language in shaping faith, values, and aspirations. English is perceived as a language of power and success. Yet, concerns over identity conflicts highlight the need for linguistic policies that balance English proficiency with preserving Islamic and national identity. Educators and policymakers must address these challenges to ensure a holistic bilingual education that fosters both religious and global engagement among students.